2021
DOI: 10.1007/s00294-020-01144-1
|View full text |Cite
|
Sign up to set email alerts
|

Spanning the gap: unraveling RSC dynamics in vivo

Abstract: Multiple reports over the past 2 years have provided the first complete structural analyses for the essential yeast chromatin remodeler, RSC, providing elaborate molecular details for its engagement with the nucleosome. However, there still remain gaps in resolution, particularly within the many RSC subunits that harbor histone binding domains.Solving contacts at these interfaces is crucial because they are regulated by posttranslational modifications that control remodeler binding modes and function. Modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Rapid RSC recruitment and histone eviction from promoters could explain why genes with FNs have more Pol II in their ORFs than SN genes. The RSC accumulation in NDRs seen in the HAT mutants but not in the tail mutants suggests that RSC can be recruited to nucleosomes using hypoacetylated (or unacetylated) tails and that subsequent acetylation might help RSC to evict histones (38,39,42,65).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rapid RSC recruitment and histone eviction from promoters could explain why genes with FNs have more Pol II in their ORFs than SN genes. The RSC accumulation in NDRs seen in the HAT mutants but not in the tail mutants suggests that RSC can be recruited to nucleosomes using hypoacetylated (or unacetylated) tails and that subsequent acetylation might help RSC to evict histones (38,39,42,65).…”
Section: Discussionmentioning
confidence: 98%
“…S2B). It makes sense considering that acetylated H3K14, a Gcn5 target, is recognized by the Sth1 bromodomain (42,64,65).…”
Section: Hats Prevent Histone Accumulation In Ndrs Genome-widementioning
confidence: 99%
“…Site‐specific in vivo crosslinking can provide valuable mechanistic insights into the effects of PTMs on chromatin dynamics involved in processes such as transcription, replication, chromosome segregation and the response to DNA damage. [ 139 ]…”
Section: Biological Insights By Processmentioning
confidence: 99%
“…Furthermore, data suggested that these interactions were negatively regulated by importin binding to a nuclear localization sequence that also resided on the C-terminus of the protein. In a more recent application of the crosslinking approach, Jain et al used pBPA scanning to characterize the binding interface and mechanistic action of the yeast RSC remodeler complex ATPase subunit, Sth1, with the nucleosome ( Figure 3 ) [ 44 , 45 ]. In this study, pBPA proved to be an effective spatiotemporal probe that allowed for detailed insights to Sth1 binding to histones.…”
mentioning
confidence: 99%
“…al. used pBPA scanning to characterize the binding interface and mechanistic action of the yeast RSC remodeler complex ATPase subunit, Sth1, with the nucleosome (Figure 3) [44,45]. In this study, pBPA proved to be an effective spatiotemporal probe that allowed for detailed insights to Sth1 binding to histones.…”
mentioning
confidence: 99%